Laubhütte Davids und Wolkensohn : eine auslegungsgeschichtliche Studie zu Amos 9,11 in der jüdischen und christlichen Exegese - Nägele, Sabine. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1995)
Laubhütte Davids und Wolkensohn deals with the history of interpretation of Amos 9:11 - a passage which is regarded in both, Jewish and Christian tradition, as a messianic prediction. The book examines its interpretation and impact in Qumran and Rabbinic Judaism as well as in the New Testament, the Church Fathers, the Middle Ages, the Reformation and in the scientific discussion up to the present. Special emphasis is laid on (a) its usage at the Apostolic Council of Jerusalem (Acts 15) and its influence on the formation of the Christian Church and (b) hitherto overlooked explicit and important interpretations of scholars such as Nicholas de Lyre, Luther, Mercerus, Miegius and Harenberg who have already made use of the rabbinic messianic interpretation of this passage. Besides, a new interpretation of Amos 9:11-15 in its historical Old Testament context is offered.